2016
DOI: 10.1186/s13054-016-1423-1
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of sepsis in hospital inpatients by ward nurses increases 30-day survival

Abstract: BackgroundSystemic inflammatory response syndrome (SIRS) and sepsis are now frequently identified by observations of vital signs and detection of organ failure during triage in the emergency room. However, there is less focus on the effect on patient outcome with better observation and treatment at the ward level.MethodsThis was a before-and-after intervention study in one emergency and community hospital within the Mid-Norway Sepsis Study catchment area. All patients with confirmed bloodstream infection have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 43 publications
0
66
0
19
Order By: Relevance
“…A study from Norway targeted early identification of in-hospital sepsis by ward nurses [8]. As part of the Mid-Norway Sepsis Study, the study assessed the impact of a bundle intervention consisting of a flow chart for sepsis identification and physician notification and a clinical tool for triage of patients exhibiting signs of sepsis and organ failure.…”
Section: Ward-based Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Norway targeted early identification of in-hospital sepsis by ward nurses [8]. As part of the Mid-Norway Sepsis Study, the study assessed the impact of a bundle intervention consisting of a flow chart for sepsis identification and physician notification and a clinical tool for triage of patients exhibiting signs of sepsis and organ failure.…”
Section: Ward-based Screeningmentioning
confidence: 99%
“…In comparison to a pre-intervention group of 472 patients with confirmed blood stream infection during a 2-year period, 409 patients with confirmed blood stream infection in a 2-year post-intervention period were found to have higher odds of surviving 30 days (odds ratio (OR) 2.7, 95% confidence interval (CI) 1.6–4.6), lower probability of developing severe organ failure (0.7, 95% CI 0.4–0.9), and, on average, 3.7 days (95% CI 1.5–5.9 days) shorter length of stay [8]. …”
Section: Ward-based Screeningmentioning
confidence: 99%
“…In a number of European countries and countries such as the USA and Australia, it is the METs and RRTs that handle such patients. When nurses identify symptoms of deterioration at an early stage, such as sepsis symptoms, earlier studies have shown an increase in the 30-day survival rate (12). A previous study by OUH, Rikshospitalet found that the nurses were satisfied with the MICN service, but did not provide reasons for use or descriptions of measures taken by the MICNs (5).…”
Section: The Aim Of the Studymentioning
confidence: 99%
“…Резуль-тат этих процессов -развитие синдрома системного воспалительного ответа, являющегося одной из «со-ставляющих» диагноза «сепсис» [11,12]. Установле-но, что ранняя диагностика сепсиса по показателям синдрома системного воспалительного ответа и со-ответственно своевременно предоставленная помощь снижают риск развития септического шока и уве-личиваеют выживаемость пациентов [13]. Однако до сих пор не найден тот «идеальный» маркер сепси-са, который отличался бы одновременно и высокой чувствительностью, и специфичностью.…”
Section: перинатология и неонатологияunclassified